2006
DOI: 10.1007/s00127-006-0122-7
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics associated with involuntary versus voluntary legal status at admission and discharge among psychiatric inpatients

Abstract: j Abstract Background The objective of this analysis was to determine the ways in which patients' legal statuses at hospital admission and discharge are associated with select sociodemographic and clinical variables. This study specifically investigated differences between patients who were voluntary during both admission and discharge, patients who were involuntary on admission but voluntary on discharge (having converted to voluntary status during hospitalization), and patients who were involuntary during bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0
9

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 23 publications
3
24
0
9
Order By: Relevance
“…Second, the most frequent diagnoses among involuntary admissions were bipolar disorder and related disorders and schizophrenia and other psychosis. Several authors confirmed our findings regarding both schizophrenia and other psychoses (Craw & Compton 2006;Bauer et al 2007;Pantusa et al 2007;Zhou et al 2015) and bipolar and related disorders (Lee et al 2007;Schuepbach et al 2008;Amr & Volpe 2012). Third, analyzing the monthly distribution of admissions, we observed a significant increase of involuntary hospitalizations during changes of season in particular in spring/summer with a peak in June.…”
Section: Discussionsupporting
confidence: 88%
“…Second, the most frequent diagnoses among involuntary admissions were bipolar disorder and related disorders and schizophrenia and other psychosis. Several authors confirmed our findings regarding both schizophrenia and other psychoses (Craw & Compton 2006;Bauer et al 2007;Pantusa et al 2007;Zhou et al 2015) and bipolar and related disorders (Lee et al 2007;Schuepbach et al 2008;Amr & Volpe 2012). Third, analyzing the monthly distribution of admissions, we observed a significant increase of involuntary hospitalizations during changes of season in particular in spring/summer with a peak in June.…”
Section: Discussionsupporting
confidence: 88%
“…Compulsory measures can weaken the therapeutic relationship and increase perceived coercion experienced by patients (Sheehan & Burns 2011). Different approaches have been developed to regulate the application of those measures -taking into account human rights, public safety, the need for adequate treatment (Salize et al 2002), and the fact that patients with mental illnesses commonly have undiagnosed or untreated medical problems (Craw & Compton 2006, Viron & Stern 2010 -to provide the most effective care and avoid negative outcomes (Kallert et al 2008). Moreover, the correct use of involuntary commitment is both a political and professional goal in terms of being a good indicator of the legal framework of the mental health care system and a marker of quality of services provided (Donisi et al 2014, Salize & Dreßing 2004.…”
Section: Introductionmentioning
confidence: 99%
“…Em serviços psiquiátricos de outras partes do globo, essa ocorrência apresenta bastante variabilidade, de 0,3% a 59,0% [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] . No Brasil, dois estudos semelhantes apresentaram valores superiores aos do presente estudo: 24,0% a 26,0% 11,30 .…”
Section: Discussionunclassified
“…Nas emergências e unidades de internação psiquiátricas, a contenção física é prática utilizada na maioria dos países, com incidências reportadas entre 0,3% a 59,0% [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] . As condições psiquiátricas que usualmente requerem indicação de contenção física são agitação psicomotora, confusão mental e agressividade ou violência em relação a si próprio, a objetos e/ou a outros e que não responderam às intervenções menos invasivas 14 , e a prevenção de quedas 18 .…”
Section: Introductionunclassified
See 1 more Smart Citation